Belgica - Demuyter, Ernest (Paris : France-Empire, 1961)
Bibliotheek Camille Huysmans
Dedicator: Demuyter, Ernest, dedicatee: Huysmans, Camille
Frans
Monografie
Keywords: ballonvaart; luchtmacht; egodocumenten